ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT JUDGEMENT DENGAN TASK COMPLEXITY SEBAGAI PEMODERASI (Studi Kasus pada Auditor Kantor Akuntan Publik di Kota Semarang) - Silmy Alfatir Karimullah; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2021)
This research examines and provides the empirical evidence of the influence of learning goal orientation, proving performance goal orientation, avoiding performance goal orientation, self-efficacy, and time budget pressure to audit judgement with task complexity as moderacy. The data were collected by using the given questionnaire to auditors from 28 public accounting firm in Semarang. The samples were selected by using a purposive sampling method. This research used multiple regression analysis as analyse of method and SPSS 25.The results from this research showed learning goal orientation, proving performance goal orientation, and self-efficacy have no significant effect on audit judgement, while avoiding performance goal orientation has a negative effect and time budget pressure has a positive effect on audit judgement. It also showed task complexity moderated the influence of learning goal orientation, proving performance goal orientation, avoiding performance, and time budget pressure on audit judgement.